Relais-accueil, un foyer pour « l’orientation » des jeunes - Francis Lebon (Sociétés et Jeunesses en Difficulté)
Relais-accueil, a community home for « orienting » young people  « Relais-accueil », a volunteer organisation located in the 13th district of Paris, helps the « young workers » in their search of housing and employment. The history of this association, between 1966 and 2006, clarifies two aspects of the policies in direction of the working class young people. On the one hand, its community home proposes a frame based on a discipline of autonomy which supposes to act and to accept the assistance of others to become oneself. On the other hand, this association is a place that brought together militants of the « Jeunesse ouvrière chrétienne » (joc) and senior official reformists who wished « to modernize » the social state. Since the eighties, town councils have been coming out as privileged interlocutors of the state, to the detriment of Relais-accueil, then little supported by the council of Paris and in the absence of senior officials mobilized since the victory of the left wing at government in 1981. Because of the rise of massive unemployment and processes of precarisation, the community home accomodates now young people older than in the past and with longer durations of stay (students, young people in training course or without employment, etc), thus prolonging their state of dependence and transition.